Larvicidal Activity of Solvent Leaf Extracts of Cassia fistula (Linn) and Clerodendron inerme (Gaertn) on the Spodoptera litura (Insecta: Noctuidae): A Potential Botanical Alternative - Muthusamy2 and Dolly Kumar1, Payal Chauhan1*, M.S. Shivakumar2, R. (Journal of Ecobiotechnology, 2011)
Spodoptera litura is a polyphagous pest affecting several agricultural crops. Chemical insecticides have been used in the past for controlling this pest. This has resulted in the development of resistance to several classes of pesticides. Bioactive molecules of plant origin hold potential alternative for the chemical pesticides. In the present study leaves of Clerodendron inerme and Cassia fistula were extracted with methanol and ethanol. The efficacy of the extracts as insecticidal agents were assessed on third instar larvae of Spodoptera litura. The results suggest that ethanol extracts of Cassia fistula (LD50 = 1.70389) and methanol extracts of Clerodendron inerme (LD50 = 3.84670) shows a higher toxicity on third instar larvae of Spodoptera litura. The present study shows that the solvent extracts from the above plants can be used for the control of armyworm.